Pelatihan Pengolahan Data Statistik Menggunakan SPSS untuk Meningkatkan Kualitas Karya Ilmiah Mahasiswa - Dina Liana; Rika Devianti; Masriani Masriani; Mardiah Mardiah; Faridatul Munawaroh; Martina Napratilora; Hendro Lisa (STAI Auliaurrasyidin Tembilahan, 2022)
There are still many students who are still reluctant to study on their own with the reason that they are unable to learn it on their own or are able to perform processing techniques but are unable to understand the process and interpret the output properly. They still need help to be able to master the technique of using software, understand the process, and correctly interpret the output of statistical data processing. The problem-solving method in this service starts from the problems that arise in the field. Moving on from these problems, we took the initiative to provide some kind of training with the aim that the problems that occur can be overcome. The Implementation of Statistical Data Processing Training Activities Using SPSS for STAI Auliaurrasyidin Tembilahan Students Semester VI to Improve the Quality of Student Scientific Work is carried out because these students will face a final project.